2016
DOI: 10.1523/jneurosci.3069-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Age Is Associated with Reduced Sharp-Wave Ripple Frequency and Altered Patterns of Neuronal Variability

Abstract: Spatial and episodic memory performance declines with age, and the neural basis for this decline is not well understood. Sharp-wave ripples are brief (ϳ70 ms) high-frequency oscillatory events generated in the hippocampus and are associated with the consolidation of spatial memories. Given the connection between ripple oscillations and memory consolidation, we investigated whether the structure of ripple oscillations and ripple-triggered patterns of single-unit activity are altered in aged rats. Local field an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 52 publications
(2 reference statements)
4
32
4
Order By: Relevance
“…Given the involvement of ripples in variable reinforcement learning (Ambrose et al, 2016), we predicted that ripple rates would increase after animals received an eye shock. We also predicted that aging would reduce the rate of ripple events and the oscillatory frequency of ripples, as has been previously reported for rest-associated ripples (Wiegand et al, 2016). …”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Given the involvement of ripples in variable reinforcement learning (Ambrose et al, 2016), we predicted that ripple rates would increase after animals received an eye shock. We also predicted that aging would reduce the rate of ripple events and the oscillatory frequency of ripples, as has been previously reported for rest-associated ripples (Wiegand et al, 2016). …”
Section: Introductionsupporting
confidence: 67%
“…Furthermore, Gerrard et al (2001) demonstrated that aged and young rats express intact memory trace reactivation during rest-associated ripples, but that the temporal organization of reactivated events is reduced in aged animals (Gerrard et al, 2008). Similarly, Wiegand et al (2016) observed reduced reactivation in aged rats, and this reduction was largely due to a reduced rate of occurrence of ripples in aged animals. Wiegand et al (2016) also demonstrated that the oscillatory frequency of ripples was reduced by approximately 15 Hz in aged animals.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations